Prediction of 90 Day and Overall Survival after Chemoradiotherapy for Lung Cancer: Role of Performance Status and Body Composition. Issue 9 (September 2017) - Bowden, J.C.S.; Williams, L.J.; Simms, A.; Price, A.; Campbell, S.; Fallon, M.T.; Fearon, K.C.H.
Abstract: Aims: If appropriate patients are to be selected for lung cancer treatment, an understanding of who is most at risk of adverse outcomes after treatment is needed. The aim of the present study was to identify predictive factors for 30 and 90 day mortality after chemoradiotherapy (CRT), and factors that were prognostic for overall survival. Materials and methods: A retrospective cohort study of 194 patients with lung cancer who had undergone CRT in South East Scotland from 2008 to 2010 was undertaken. Gender, age, cancer characteristics, weight loss, body mass index (BMI), performance status (Eastern Cooperative Oncology Group; ECOG) and computed tomography-derived body composition variables were examined for prognostic significance using Cox's proportional hazards model and logistic regression. Results: The median overall survival was 19 months (95% confidence interval 16.3, 21.7). Four of 194 patients died within 30 days of treatment completion, for which there were no independent predictive variables; 22/194 (11%) died within 90 days of treatment completion. BMI < 20 and ECOG performance status ≥2 were independent predictors of death within 90 days of treatment completion ( P = 0.001 and P = 0.004, respectively). Patients with either BMI < 20 or ECOG performance status ≥ 2 had an odds ratio of death within 90 days of 5.97 (95% confidence interval 2.20, 16.19), rising to an odds ratio of 13.27 (1.70, 103.47) for patients with both BMI < 20 and ECOG performance status ≥ 2. Patients with low muscle attenuation had significantly reduced overall survival ( P = 0.004); individuals with low muscle attenuation had a median survival of 15.2 months (95% confidence interval 12.7, 17.7) compared with 23.0 months (95% confidence interval 18.3, 27.8) for those with high muscle attenuation, equating to a hazard ratio of death of 1.62 (95% confidence interval 1.17, 2.23, P = 0.003). Conclusion: Poor performance status, low BMI and low muscle attenuation identify patients at increased risk of premature death after CRT. Risk factors for adverse outcomes should inform personalised discussions with patients about the potential harms as well as the intended benefits of treatment. Highlights: Low body mass index and poor performance status predict reduced 90 day survival. Low muscle attenuation (myosteatosis) is prognostic for overall survival. Few patients are underweight despite evidence of active cachexia. Personalised clinical decision making should incorporate known prognostic factors.